Assessment of Wave Characteristics in National Water Borders for Tactical Vessel Analysis and Maritime Security - Muhammad Farhan Rahmat; Husein Syahab; Amalia Ika Wulandari; Cahya Kusuma; Mahendra Indiaryanto; Muhammad Anjas Syam; Fernanda Wahyu Pratama; Firman Noor (Indonesian Journal of Maritime Technology, 2026)
This study addresses the challenge of accurately representing wave conditions in Indonesian waters for ship design, where conventional standards based on North Atlantic extremes may lead to over-conservative designs. The objective is to evaluate seasonal wave characteristics in four representative regions—North Natuna Sea, Ambalat Block, Timor Sea, and Arafura Sea—and assess their implications for ship operational reliability. Hourly wind and wave data for 2025 were obtained from ERA5 reanalysis, while bathymetric information was sourced from BATNAS. Analyses included directional distribution (wind and wave rose), temporal variability of significant wave height (Hsig) and peak period (Tp), wave energy estimation using linear wave theory, and comparison between empirical data and analytical probability models via a Weibull distribution. Results show that the North Natuna Sea experiences the highest wave loading (Hsig up to 4.450 m; energy 13.316 kW/m) due to long fetch and bathymetric shoaling. Ambalat Block exhibits minimal wave energy (0.850 kW/m) despite deep waters, indicating fetch-limited growth. Timor Sea presents moderate Hsig (1.5–2.3 m) with long wave periods (>20 s) driven by swell, while Arafura Sea shows high Hsig (2.663 m) and energy (5.526 kW/m), though shallow-water effects limit wave growth and increase wave steepness. These findings demonstrate that wave loading is controlled not only by height, but also by period and bathymetric transformation. Incorporating site-specific and seasonal wave characteristics is essential for realistic and efficient ship design and operational assessment.